Pembinaan instrumen penilaian kendiri pembelajaran Algebra tingkatan empat - Abdullah Mohd Faizal Nizam Lee, Low Chai Peng, Dollah Mohd Uzi, (Universiti Pendidikan Sultan Idris, 2016)
Pembinaan instrumen penilaian kendiri pembelajaran Algebra tingkatan empat by Abdullah Mohd Faizal Nizam Lee, Low Chai Peng, Dollah Mohd Uzi,